The role online review on mobile commerce adoption: an inclusive growth context - Pipitwanichakarn, Tanikan; Wongtada, Nittaya (Journal of Asia business studies, 2020)
Purpose As technology has increasingly disrupted traditional commerce, there is a need for inclusive growth to ensure that no group – particularly the underprivileged – is left behind. Against this backdrop, this paper aims to shed light on mobile commerce (m-commerce) adoption among street vendors. This study conducts an experiment to investigate the contribution of online reviews and relevant factors in enhancing the perceived usefulness and adoption of m-commerce. Design/methodology/approach This study used a 2 (perceived ease of use: high vs low) × 2 (trust in service provider: high vs low) × 2 (online review: positive vs negative) between-subjects design, resulting in eight experimental groups. The level of the online review was manipulated, and the degrees of perceived ease of use and trust were measured. Findings Perceived usefulness depends on online reviews when users perceive incongruent information (e.g. high ease of use but low trust); that is, users who saw positive reviews more strongly perceived the usefulness of m-commerce. On the contrary, perceived usefulness does not vary based on online reviews if users perceive congruent information (e.g. high ease of use and high trust). Originality/value This research advances the knowledge of m-commerce adoption by exploring the interaction of perceived ease of use, trust and online reviews, a combination that has not been addressed in previous empirical studies.